Financial Health Analysis of Sharia National Pension Savings Bank (Bank BTPN Sharia) in terms of Capital Factor (CAR), Financing (FDR), Profitability (ROA, ROE, NPM & BOPO) and Financing Risk (NPF) - Balele, Bintang; Pasryb, A. Syahida Ulhaq (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The study aims to analyze financial health of Sharia National Pension Savings Bank (Bank BTPN Sharia) in terms of Capital Factor (CAR), Financing (FDR), Profitability (ROA, ROE, NPM & BOPO) and Financing Risk (NPF). The study applied quantitative descriptive method. The data obtain from the period between 2015 and 2019. The criteria used to assess the soundness level of a bank in this study were based on Bank Indonesia circular letter No. 13/24 / DPNP 2011. The result in this research indicates that Sharia National Pension Savings Bank (Bank BTPN Sharia) in terms of Capital Factor (CAR), Financing (FDR), Profitability (ROA, ROE, NPM & BOPO) and Financing Risk (NPF) are in good health.